Critical Consciousness and Schooling: The Impact of the Community as a Classroom Program on Academic Indicators - D. Gavin Luter; Austin M. Mitchell; Henry L. Taylor (MDPI AG, 2017)
The present study investigates the extent to which a program guided by the principles of critical pedagogy, which seeks to develop critical consciousness, is associated with the improved academic performance of students attending a low-performance middle-school in Buffalo, New York. The students were enrolled in an in-school academic support program called the Community as Classroom, which used critical project-based learning to show students how to improve neighborhood conditions. The study found that the Community as Classroom program bolstered student engagement as reflected in improved attendance, on-time-arrival at school, and reduced suspensions. Although class grades did not improve, standardized scores, particularly in Math and Science, dramatically improved for these students from the lowest scoring categories. We suspect that given increased student engagement and dramatically improved standardized test scores, teacher bias might be the cause of no improvements in class grades. We conclude that critical pedagogy, which leads to increased critical consciousness, is a tool that can lead to improved academic performance of students. Such a pedagogy, we argue, should be more widely used in public schools, with a particular emphasis on their deployment in Community Schools.